Ekonomicheskaia otsenka problematiki avtorskogo prava v oblasti dizaina - Smetanina T. V. (Science, education, society: trends and prospects, 2018)
Design is a special kind of activity in the field of copyright creation. Protecting the object of copyright in design allows you to increase the activity of authors in this area. With the protection of copyright on the results of intellectual and creative work is directly related to the effectiveness of the country's economy as a whole. Design from an economic point of view is a special area of activity in which the creative potential of an individual is realized. The more actively the sovereign territory supports this direction of realization, the more successfully the area of the economy of the sovereign territory relating to intangible assets develops. In the modern world, this determines the level of development of the technological potential of a sovereign territory, the level of its competitiveness and economic security. The development of intangible assets should be based on the experience of the most developed sovereign territories in this regard. Comparison and analysis of cop
Keywords: конкурентоспособность; интеллектуальная собственность; дизайн; экономическая безопасность; индивид; защита; деловая репутация; нематериальные активы; intellectual property; competitiveness; design; economic security; intangible assets; творческий труд; creative work; individual; интеллектуальный труд; protection; intellectual work; business reputation